VD_FINDINFO Jug / 2015 / 450 vom 20. Februar 2015 - VD Tribunal cantonal (2015)
CONTRAINTEDROIT PÉNAL, TENTATIVEDROIT PÉNAL, DIFFAMATION, FIXATION DE LA PEINE | 173 ch. 1 CP, 181 CP, 22 ad 181 CP, 47 CP